Some observations on sea water circulation in the area of the Danube mouths - Nae, Ion; Postolache, Iulian (Cercetări Marine - Recherches Marines, 2026)
The paper analyses the results of direct marine current measurements carried out off the mouths of the Danube in April and September 1977, corresponding respectively to periods of high and low Danube water discharge. The main factors acting on the regime of the currents within different water layers are considered: wind, river discharge and shoreline direction. The existence of a general southward flow up to 12-15Nm width has been finally pointed out.